2022
DOI: 10.1007/s00705-022-05509-4
|View full text |Cite
|
Sign up to set email alerts
|

Predominance and first complete genomic characterization of canine parvovirus 2b in Turkey

Abstract: Viral enteritis is a significant threat to domestic dogs. The two primary pathogens that cause viral enteritis in dogs are canine coronavirus (CCoV) and canine parvovirus (CPV). In this study, we investigated the occurrence of CPV-2, CCoV, and canine circovirus coinfection by characterizing circulating subtypes of CPV-2 in faecal samples from symptomatic dogs admitted to veterinary clinics located in Ankara, Elazığ, Kayseri, and Kocaeli provinces of Turkey, between 2019 and 2022. Virus detection by PCR and RT-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 63 publications
2
7
0
Order By: Relevance
“…In contrast, the CPV-2a / 2b variants which exhibited Thr440→Ala variations were without Gln370Arg variation. Such documentations were also reported by other researchers [45,46]. Similarly the few CPV-2a variants with Thr440 are also observed with Gln370Arg variation (CPV-2a 370Arg variant).…”
Section: B Cell Epitope Predictionsupporting
confidence: 86%
“…In contrast, the CPV-2a / 2b variants which exhibited Thr440→Ala variations were without Gln370Arg variation. Such documentations were also reported by other researchers [45,46]. Similarly the few CPV-2a variants with Thr440 are also observed with Gln370Arg variation (CPV-2a 370Arg variant).…”
Section: B Cell Epitope Predictionsupporting
confidence: 86%
“…The CPV-2b positivity (48/62) and canine circovirus (CCV) and canine coronavirus (CCoV) negativity (0/62) of these samples were confirmed in the previous epidemiological survey [ 30 ]. Template DNA was extracted from the supernatants of the fecal samples using a commercial extraction kit (MinElute Virus Spin Kit, QIAGEN, Hilden, Germany), following the manufacturer's instructions.…”
Section: Methodssupporting
confidence: 66%
“…In Humans, based on VP1 and VP2 sequences, three genotypes, HBuV-1, HBuV-2, and HBuV-3, have been determined; different genotypes of this virus show ıt had the highly diverse capsid gene [ 40 ]. VP2 of the carnivore protoparvoviruses is a significant capsid protein vital in determining antigenicity, host range, and tissue tropism [ 8 , 30 ]. When the VP2 protein of the selected canine Bufaviruses in this study was examined, more than 50 substitutions were detected, and 16 were specific for CBuV-2.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, many studies have attempted to detect the virus, especially in wild animals. Molecular studies on dogs have found three variants of CPV in local circulation in different regions of Turkey [ 20 , 21 , 28 – 32 ]. However, no reports of any types of CPV were found in wild carnivores, such as foxes, wolves, and coyotes, from our country.…”
Section: Discussionmentioning
confidence: 99%